2004
DOI: 10.1080/02699050410001672396
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive training in home environment

Abstract: The study indicates that home-based cognitive training improves some attentional and memory functions and facilitates learning of strategies. Future controlled studies are needed to confirm the results and analyse the efficacy of different aspects of home-based training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 37 publications
1
57
0
1
Order By: Relevance
“…The lack of improvement in the declarative memory task suggests that the training specifically targets WM, not memory in general. This is consistent with the negative result on the same declarative memory test from another study on attention training after brain injury: Boman et al [22], which also found significant (within group) pre-post training differences on more complex attention tests but not on the test for declarative memory.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The lack of improvement in the declarative memory task suggests that the training specifically targets WM, not memory in general. This is consistent with the negative result on the same declarative memory test from another study on attention training after brain injury: Boman et al [22], which also found significant (within group) pre-post training differences on more complex attention tests but not on the test for declarative memory.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies investigated the effectiveness of attention training in the chronic stage (>1 year) after brain injury in adults [15][16][17][18][19][20][21][22]. For a review see Cicerone et al [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Lustig et al (2009) defined process training as tasks Bthought to load heavily on a specific cognitive process^such as working memory or executive function (p. 507). Process training can include exercises targeted at improving speed of processing, attentional breadth, dualtasking, task-switching, or motor skills (Boman et al 2004;Lustig et al 2009). Such approaches often involve repeated drills or perceptual-practice exercises of the basic cognitive ability targeted in training (Morrison and Chein 2011).…”
Section: Abstract Aging Cognitive Training Brain Fitness Brain mentioning
confidence: 99%
“…Evidence shows that the use of process-training materials designed on the basis of neuropsychological theories and arranged into a structured programme can lead to gains in the majority of patients (Boman et al, 2004). Studies have also highlighted the benefits of using computerised assessment and rehabilitation tools in memory process training (Moore et al, 2001;Tam & Man, 2004;Cappa et al, 2005).…”
Section: Process Trainingmentioning
confidence: 99%
“…These include both general memory problems such as learning and retrieval, and specific problems with orientation, dates, names, faces, routes or appointments (Wilson et al, 2001;Boman et al, 2004;Ávila et al, 2004). Rose & Brooks (2003) have highlighted the potential role of virtual reality paradigms in memory rehabilitation.…”
Section: Rehabilitation Techniques and Strategiesmentioning
confidence: 99%